Optimizing Management Functions in Supervision in the Heart Room of H. Abdul Manap Hospital, Jambi City - Marta, Marta Prima Yuda; Mawarti, Indah (Program Studi Keperawatan Fakultas Kedokteran dan Ilmu Kesehatan Universitas Jambi, 2024)
Supervision is a management function of direction that needs to be carried out by nurse managers in a structured and systematic manner. Supervision is an activity of the direction function. Supervision in the Heart Room of H. Abdul Manap Hospital, Jambi City requires planning for making a structured schedule, so that it can be implemented properly and can improve health services appropriately and professionally. In this problem, it will have an impact on the level of service and differences in perception between subordinates and superiors if problems occur. The study used observation and interview methods. The intervention was carried out for 2 days as an alternative to solving this problem, namely making a permanent supervision schedule in the room. During the 5 days of observation, supervision has been carried out in the room according to the previously made schedule. It is hoped that this can provide a reference and be useful as a guideline regarding the supervision schedule in the room so that supervision can be carried out routinely and become more optimal.